Arranging blood for elective thyroid surgeries: dilemma continues in the developing world. (December 2017) - Faridi, Salman; Ahmad, Aman; Beg, Mirza; Siddiqui, Faisal; Edhi, Muhammad; Khan, Mehmood
Abstract Background Cross matched blood is frequently ordered based on a subjective anticipation of blood loss for a procedure. Excessive blood arrangement and wastage overburdens the blood bank in terms of work load and storage of blood, increases cost of medical care and results in injudicious use of a limited resource. The aim of this short report is to assess the current practice for arranging cross matched blood in elective thyroid surgeries by comparing cross match to blood transfused ratio. Findings Medical records for all patients from January 2009 to December 2014 undergoing thyroid surgery were retrieved and reviewed through electronic health information management system (HIMS). A total of 91 patients were included in the study, out of which 18 (19.7%) were male and 73 (80.2%) were female. A total of 107 units of blood were arranged and only 9 were transfused. 47 patients underwent a total thyroidectomy, while 44 underwent a hemithyroidectomy. The cross match to transfusion ratio came out to be 11.88. Conclusions Routine arrangement of cross matched blood is not required in elective thyroid surgeries. All institutions should have a maximum blood ordering schedule planned for elective procedures, and blood products should be arranged accordingly to avoid unnecessary cross matching.